The impact of the economic and technological factor on the foreign policy of South Korea - Ibrahim, Nahlah Ismael (Journal of Economic, Administrative and Legal Sciences, 2022)
With the end of World War II in 1945, Korea was divided into two parts, South Korea and North Korea, then the Korean War soon broke out between the two countries and lasted until 1953. After the war, South Korea began rebuilding its economy based on the investment of human resources in a correct manner, as well as investing conditions The local and international economy, and the state's intervention in the economy played a major role in transferring the Korean economy to the ranks of the best economies in the world.The aim of the research is to highlight the strength and weakness of the Korean experience in the economic and technological field and to confront the challenges that have been laid mainly for it in overcoming the difficulties in the field of debt repayment by increasing exports to global markets. For this reason, Korea has become a magnet for production companies as it is one of the main centers of production.Then he touched on the reasons for the success of economic and technological renewal in South Korea and how this country reached the horse of states in terms of modernity and modernization in brief by dividing the research into a theoretical framework and then addressing the importance of the economic and technological factor
Keywords: the economic factor; the technological factor; foreign policy; the Korean miracle